2002
DOI: 10.1137/s0036139901383826
|View full text |Cite
|
Sign up to set email alerts
|

Self-Similar Solutions for Weak Shock Reflection

Abstract: We present numerical solutions of a two-dimensional Riemann problem for the unsteady transonic small disturbance equations that provides an asymptotic description of the Mach reflection of weak shock waves. We develop a new numerical scheme to solve the equations in selfsimilar coordinates and use local grid refinement to resolve the solution in the reflection region. The solutions contain a remarkably complex structure: there is a sequence of triple points and tiny supersonic patches immediately behind the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
84
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(105 citation statements)
references
References 20 publications
21
84
0
Order By: Relevance
“…When analysing the contours in Fig. 2b, indication is given of the possible existence of at least two supersonic patches along the Mach stem further satisfying Tesdall and Hunter's [9] observations, and the formation of a GMR.…”
Section: Introductionsupporting
confidence: 61%
See 3 more Smart Citations
“…When analysing the contours in Fig. 2b, indication is given of the possible existence of at least two supersonic patches along the Mach stem further satisfying Tesdall and Hunter's [9] observations, and the formation of a GMR.…”
Section: Introductionsupporting
confidence: 61%
“…This resulted in the region behind the triple point being better resolved and the supersonic patch to be identified. For incident shock Mach numbers ranging from 1.05 to 1.1 on a 10 • ramp, their results clearly detected the fourth wave, namely the expansion fan, and an indication of a shock terminating the expansion wave as predicted in [9]. The authors advised that the observed four-wave structure be referred to as Guderley reflection.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…This brings up Euler system's von Neumann triple point paradox, for which John Hunter and collaborators have produced numerical evidence of Guderley reflection [10,35,36]. See Skews and Ashworth [30] for physical experimental evidence.…”
Section: Initial Datamentioning
confidence: 98%